Fluid simulation of dust-acoustic waves in space dusty plasmas - Singh, Kuldeep; Kakad, Bharati; Kakad, Amar; Kourakis, Ioannis (My University, 2022)
The omnipresence of charged dust in space plasmas has engendered a conspicuous interest since the preliminary observations of radial spokes in Saturn's rings by the Voyager spacecraft [1]. It is by now established, both theoretically and experimentally, that the presence of extremely massive and highly charged dust grains may not only lead to significant modification of the characteristics of known plasma modes, and also electrostatic solitary waves (ESWs) and associated instabilities space/astrophysical environments [2], but it also gives rise to novel modes that wouldn't exist in its absence. One fundamental representative of this wide range of possibilities in plasma dynamics, the dust-acoustic (DA) wave, is a low-frequency electrostatic oscillation that is entirely sustained due to the dust inertia, while the restoring force is provided by the light particle (electron, ion) plasma components [1]. \par Theoretical plasma models based on either perturbative or non-perturbative analytical methods have proven valuable in deriving analytical solutions representing dust acoustic wave structures. However, although these techniques do provide "static" predictions of dust acoustic solitary waves, they do not address their generation mechanism, nor do they test the dynamics and stability profile of the predicted waveforms. To tackle these limitations, one inevitably has to resort to computer simulation in order to understand the evolution of nonlinear solitary waves [3-6]. In this study, we have performed a series of one-dimensional fluid simulations to investigate the evolution and the characteristics of dust acoustic waves (DAWs) in a plasma comprised of inertial dust, superthermal electrons and ions. An ad hoc initial density perturbation in the equilibrium ion density is used to excite DA pulses in our model (superthermal) dusty plasma. Our simulation algorithm provides a comprehensive illustration of the evolution of all state variables associated with DA waves. Our main focus is to understand the role of dust in the nonlinear evolution of DA waves in the presence of accelerated (superthermal) electrons and ions in a non-Maxwellian background (distribution). This is an ubiquitous situation in e.g. the solar wind [7]. Our observation corroborates the fact that the dust concentration, the dust charge state and the superthermal index of the background particles play a pivotal role in the formation of DA solitary waves. These results will be helpful in understanding the characteristics of DA ESWs in space plasmas, especially in the planetary rings and cometary tails [1-2, 8]. \par Acknowlegments: The authors gratefully acknowledge financial support from Khalifa University of Science and Technology, Abu Dhabi UAE via the (internal funding) project FSU-2021-012/8474000352. This work was initiated and carried out during a visit by one of us (AK) to KU; the hospitality offered by the host is greatly acknowledged. Funding from the Abu Dhabi Department of Education and Knowledge (ADEK), currently ASPIRE UAE, via the AARE-2018 research grant ADEK/HE/157/18 is acknowledged. The author(s) wish to acknowledge the contribution of Khalifa University's high-performance computing (HPC) and research computing facilities to the results of this research. References: [1] P. K. Shukla and A. A. Mamum, Introduction to Dusty Plasma Physics (IoP Publ, Bristol, UK, 2002). [2] C. K. Goertz, Rev. Geophys. 27, 271 (1989), M. Horanyi & D.A. Mendis, Astrophys. J. 307, 800 (1986). [4] A. Kakad, A. Lotekar, B. Kakad, Phys. Plasmas 23, 110702 (2016). [5] A. Lotekar, A. Kakad, B. Kakad, Commun. Nonlinear Sci. Numer. Simul. 68, 125-138 (2019). [6] K. Singh, A. Kakad, B. Kakad, N.S. Saini, MNRAS 500, 1618 (2021), idem, EPJ Plus. 136, 14 (2021). [7] V. Formisano, G. Moreno, F. Palmiotto, J. Geophys. Res. 86, 8157 (1973). [8] C. K. Goertz, Linhua-Shan, and O. Havnes, Geophys. Res. Lett. 15, 84 (1988).
Keywords: Electrostatic solitary waves; Dust acoustic waves; Space dusty plasmas